MITOS LORELEI DARI WAKTU KE WAKTU: KAJIAN FEMINISME EKSISTENSIALISME PADA TIGA LIRIK LORELEI TAHUN 1823, 1981, DAN 2013 - Griselda Febrina Talitha; Lisda Liyanti (Universitas Sebelas Maret, 2019)
This study analised the theme of the myth contained in three lyrics of Lorelei from three different times. Lorelei is a mythical woman whose name is taken from a cliff on the Rhine. This research will refer to the relationship between women (Lorelei) and male figures and the relation will be analyzed through the perspective of existentialist feminism using two main concepts, Men as Subjects and Women as Other Figures. The author chose the Lorelei-lyrics from three different time, Heinrich Heine's Lorelei (1823), Dschinghis Khan's Loreley (1981), and Faun's Lore Lay (2013) to show the Lorelei myth displayed in different era. Through the study of existentialism feminism, it can be seen that Lorelei is still described as the object which is marginalized by the strong myth of the fame fatale. Although the depictions of Lorelei's subjectivity can be found in some parts of the lyrics by Dchingis Khan (1981) and Faun (2013), but those depictions are still very vague. Keywords: Myth, Lorelei, Existentialism Feminism, Men, Women